Experimental Assessment of the Seismic Response of a Base-Isolated Building Through a Hybrid Simulation Technique - Furinghetti, Marco; Lanese, Igor; Pavese, Alberto (Frontiers in Built Environment, 2020)
Base-isolated structural systems have been more and more investigated through both numerical and experimental campaigns, in order to evaluate the effective advantages, in terms of vulnerability reduction. Thanks to the lateral response of proper isolation devices, large displacement demands can be accommodated, and the overall energy of the seismic event can be dissipated, by means of hysteretic behaviors. Among the common typologies of isolators, Curved Surface Slider devices represent a special technologic solution, with potentially high dissipative capacities, provided by innovative sliding materials. On the other hand, the overall behavior is highly non-linear, and a number of research works have been developed, aiming at the definition of the most comprehensive analytical model of such devices. The most realistic response of a base-isolated structure could be returned by a shake table test of a full-scale buildings. However, dimensions of the available shake tables do not allow to consider the common load conditions, which the isolation devices are subjected to, and consequently scaled specimens are needed, and unrealistic responses could be found. Hybrid simulations seem to solve such an issue, by accounting for an experimental sub-structuring, represented by a physical devices tested in a testing equipment, and a numerical sub-structuring, consisting of a numerical model of the superstructure. Thus, a much more realistic response of the full-scale structure can be computed. In this work the outcomes of a number of hybrid simulations have been deeply analyzed, and compared to similar numerical model, by accounting for proper non-linear constitutive laws for isolation devices, in order to evaluate the effectiveness of design and assessment procedures, commonly adopted in real practice applications.